1981
DOI: 10.2151/jmsj1965.59.4_535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cumulus Convection on the vorticity Field in the Tropics

Abstract: The large-scale budget of vorticity over the Marshall Islands area is reexamined based on wind data during the period April-July 1956. Efforts are made to obtain accurate estimates of the horizontal advection and twisting terms in the vorticity equation. The mean vertical profile of the budget residual for disturbed conditions shows a large apparent source of positive vorticity in the upper troposphere and a sink near the surface. However, this mean profile is more complicated than those previously obtained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…As described in the literature (e.g. Reed and Johnson, 1974; Chu et al , 1981), regions with significant convective activity show an apparent source of cyclonic vorticity in the upper troposphere and an apparent sink near the surface, suggesting a vertical transport of vorticity by convective processes.…”
Section: Methodsmentioning
confidence: 99%
“…As described in the literature (e.g. Reed and Johnson, 1974; Chu et al , 1981), regions with significant convective activity show an apparent source of cyclonic vorticity in the upper troposphere and an apparent sink near the surface, suggesting a vertical transport of vorticity by convective processes.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies (HOLOPAINEN and OORT, 1981;CHU et al, 1981) revealed that the horizontal transport and the production terms (stretching and tipping) are signi®cant in the vorticity budget.…”
Section: Vorticity Budgetmentioning
confidence: 99%
“…The budget terms show that the horizontal transportation of vorticity is eectively balanced in the monsoon region by the production of vorticity through sub-grid scale processes such as cumulus convection. Earlier studies (WILLIAMS and GREY, 1973;REED and JOHNSON, 1974;CHU et al, 1981) have delineated that the cumulus convection in the tropics could generate a large apparent source of positive vorticity.…”
Section: Vorticity Budgetmentioning
confidence: 99%
“…Some studies (HOLOPAINEN and OORT;CHU et al, 1981) reveal that the horizontal transport and the production term (stretching and tipping) are significant in the vorticity budget. The geographical distributions of vertically integrated vorticity budget terms are presented in Figure 8.…”
Section: Vorticity Budgetmentioning
confidence: 99%